Criminalized or Medicalized? Examining the Role of Race in Responses to Drug Use. (3rd August 2021) - Lindsay, Sadé L; Vuolo, Mike
Abstract: Drug policy has shifted from intense criminalization toward reforms that prioritize decarceration and treatment. Despite this shift, little is known about whether support for recent treatment-oriented drug policy is equitable by users' race and the drug type. Using the opiate and crack cocaine crises as cases, we analyze 400 articles from the New York Times and Washington Post to assess the degree to which the two crises were racialized, criminalized, and medicalized. We find that media coverage medicalized and humanized White people who use opiates, while coverage of crack cocaine focused on criminalization, vilifying Black people who use drugs. We then conduct two vignette experiments (N=308; N=630) to examine whether these racialized frames shape public support for treatment or criminalization. We find the public more likely to support criminalization for Black people, while supporting drug treatment for White people. Respondents are more likely to support drug treatment for heroin use than for crack cocaine. Our findings suggest that support for medicalized approaches to drug use is more likely to occur for White people and drugs linked to White people, while Black people and drugs associated with Black people continue to be perceived as largely amenable to punitive options.